(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article emphasizes the incomparable importance of Kurash in the comprehensive upbringing of a healthy generation, strengthening the country’s defense power, and improving military art. If we may say so, Kurash is one of the historical values that form a united nation and a united people. Kurash is not only a physical competition between two athletes, but also a means of educating young people in the spirit of national and universal values. In terms of the content of Kurash, its rules embody the ideas of sports ethics and humanity, such as courage, patriotism, honesty, fairness, recognition of victory and defeat, respect for the opponent, coaches, spectators, and judges.